The effects of conditionality monitoring on educational outcomes: Evidence from Brazil's Bolsa Família programme - Luis Henrique Paiva; Fábio Veras Soares; Flavio Cireno; Iara Azevedo Vitelli Viana; Ana Clara Duran (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
Conditional cash transfer programmes have been increasingly adopted by several lowand middle-income countries. Despite this overall acceptance, conditionalities remain under scrutiny regarding their possible independent effects on educational and health indicators. This paper is an ecological study of conditionalities in Brazil's Bolsa Família programme. As programme coverage (taken as a proxy of cash transfers) and monitoring and enforcement of the educational conditionalities (proxy of conditionalities) are not correlated at the municipal level, this study fits a number of different ordinary least square (OLS) and growth-curve models to explain variations in drop-out rates and school progression in basic education in public schools across municipalities. [...]
Keywords: 330; effects; conditionality; monitoring; educational outcomes; evidence; Brazil; Bolsa Família programme